ANALISIS MIKROBIOLOGI BEBERAPA SUSU KEDELAI TANPA MEREK YANG BEREDAR DI KABUPATEN MAROS SULAWESI SELATAN - Santri Santri; Siska Nuryanti; Tadjuddin Naid (Fakultas Farmasi UMI, 2015)
Research about the micribiological analyze has been of some soys milk without brand marketed in Maros, South Sulawesi. The research to be compared with the requirements that have been determined by the director-general of the POM. The research conducted by determining the number plate total (ALT) bacteria, Total Plate Number (ALT) moulds as well as the presence of microbial pathogens in some soys milk without brand. The research methods using Standard Plate Count (SPC) to calculate the total amount of bacteria and mold, as wel as the identification method to determine the number of pathogenic bacteria. The results of this study indicating that the sample of C, E and H microbial has fulfilled the requirements of soy milk pathogenic bacteria test of Coliform (-), Salmonella sp (-), Staphylococcus aureus (-) and Bacillus cereus (-). Sample C, E and H has fulfilled the requiremqnts of ALT bacteria and sample C has fulfilled the requiremqnts of ALT moulds. But the E dan H sample have has not fulfilled the requirements.